Development of robust control scheme for wheeled mobile robot in restricted environment - Muhammad Sawal, A Radzak (2021)
This research is aimed to develop a wheeled mobile robot (WMR) that is able to track reliably and robustly a certain trajectory in a constrained environments. The control of MWR in the restricted areas during path execution still a complicated problem in robot researches, since it needs to maintain the tracking errors at the zero level and the wheel mobile robot must follow robustly the pre-defined path using a suitable control system; otherwise it can cause to crash robot with other objects. A novel algorithm so called laser simulator logic (LSL) has been develo ped to estimate the inertia moment when the environment is noisy and cannot use fuzzy logic algorithm. This algorithm gives the possibility to calculate the membership function with highly overlapped linguistic variables and thus remove the noise. The proposed LSL is then integrated with existing Active Force Control (AFC) and PD to ensure good closed loop performance and reject the noise and disturbances. A simulation study of WMR control in pre-planned paths in two environments namely, zigzag and highly curved terrains, has been conducted to verify the proposed algorithm and compare it with other existed algorithms. Thus, a new WMR prototype with four wheels, two differential and two castor wheels has been designed, fabricated and inspected in the laboratory. The WMR is equipped with two sensors, encoders and current sensor, and direct current (DC) motor to perform the required path in the constrained environments. An embedded controller has been used to integrate the platform components such electronics co mponents, mechanical components and computer programs with appropriate interfacing structure. PD-AFC controller system employing the use of three feedback control loops, namely, internal, external and quick compensation loops, have been used to compensate the disturbance in constrained environments. The external loop is used to control the kinematics parameters of the control system via PD controller, However, the internal loop is used to control the dynamic of robot and disturbance rejection via AFC controller. On the other hand, a quick compensation loop has been introduced to compensate the difference between the reference and actual acceleration via PD controller. The results of simulation show that the proposed algorithm has the best performance among a ll controllers either in zigzag or circular environments, especially when the disturbances are applied. To confirm the results of simulation for the proposed algorithm, a real-time experiments in circular path has been conducted to show that the proposed controller scheme is robust enough in the real -time control and able to track the robot effectively on its reference path. The experimental results work show the capability of the proposed algorithms and the new controller to robustly move the WMR in the constrained environments, thereby it verifys the simulation counterpart.